Hemodynamics in Coronary Arteries: using Open-Source Software-Simvascular to Investigate the Hemodynamics in Coronary Arteries of the Patient-Specific Modeling - Thi Dung, Nguyen; Thi Hue, Pham; Thi Cam Nhung, Do; Van Sang, Pham (Vietnam Journal of Science and Technology, 2024)
Patient-specific cardiovascular simulation is emerging as a potent tool for basic, translational, and clinical research and has established itself as a paradigm in the field of cardiovascular science. The SimVascular software package, considered a state-of-the-art open-source package, offers a comprehensive pipeline from medical imaging data segmentation to patient-specific blood flow simulation and analysis. In this study, we employ SimVascular to explore a model of coronary arteries in a young and healthy 24-year-old woman. The outcomes of the entire simulation process encompass the assessment of flow and pressure waveforms at both the outlet of the aorta and the coronary arteries, which serve as indicators of blood flow qualities within these vessels. Given the pivotal role of wall shear stress in the development of arterial plaque, SimVascular employs the finite element method to solve the governing equations of incompressible viscous fluids. This approach effectively tackles the Navier-Stokes equations along the vessel wall using meticulously constructed mesh components. Additionally, this paper delves into the issue of cardiovascular blood vessel dynamics via an analysis of wall shear stress data).